Graphene-based Biosensors for Biomolecules Detection - Zheng, Qing; Wu, Hao; Wang, Nan; Yan, Rui; Ma, Yuehui; Guang, Weijun; Wang, Junzhong; Ding, Kejian (Current Nanoscience, 2014)
Recent years have witnessed various breakthroughs in the research of graphene-related materials since the emergence of a few promising techniques for large-scale production of mono- or multi-layer graphene films. With the help of various surface modification methods, the physicochemical properties of graphene are greatly improved and graphene shows superior sensitivity and selectivity for biological molecular analysis. This paper selectively reviews the application of graphene-based biosensors, especially for detecting nucleic acid, protein and biological small molecules. In addition, future perspectives of graphene-based biosensors are also prospected.
Keywords: protein